2003
DOI: 10.1177/0734371x02250113
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Variation in the Practice of Employee Discipline

Abstract: First-line supervisors' responses to employee-related problems can vary widely from one supervisor to another. Assuming fair and consistent disciplinary activity is valued by organizations, then discovery of the factors causing supervisors to respond differently to similar situations is a valuable activity. Using a case study approach for four organizations in Puerto Rico, this article explores how factors such as sector, union presence, and managerial and human resource department support influence the choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…As Rivas (1991) put it "[T]he organization of the work force and the presence of labor unions tend to require managers to exercise due process in disciplinary actions" (p. 191). When policies are clear, understood, and accepted as valid, supervisors are more likely to follow formal disciplinary policies (Pagan & Franklin, 2003). Of course, the supervisor may utilize formal discipline practices because higher management has signaled, through the allocation of resources and time, that it supports formal actions and will sanction those who do not conform.…”
Section: Organization Culture Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…As Rivas (1991) put it "[T]he organization of the work force and the presence of labor unions tend to require managers to exercise due process in disciplinary actions" (p. 191). When policies are clear, understood, and accepted as valid, supervisors are more likely to follow formal disciplinary policies (Pagan & Franklin, 2003). Of course, the supervisor may utilize formal discipline practices because higher management has signaled, through the allocation of resources and time, that it supports formal actions and will sanction those who do not conform.…”
Section: Organization Culture Literaturementioning
confidence: 99%
“…Merit Systems Protection Board [U.S. MSPB], 1992). Pagan and Franklin (2003) reported that 83% of supervisors interviewed in a public organization in Puerto Rico relied on informal rather than formal strategies when dealing with disciplinary issues.…”
Section: Employee Discipline In the Literature And In Practicementioning
confidence: 99%
See 1 more Smart Citation